Percutaneous Internal Drainage in Symptomatic Renal Parapelvic Cyst Refractory to Sclerotherapy: A Case Report: Novel Percutaneous Internal Drainage for Renal Cyst - Park, Suyoung; Kim, Jeong Ho; Hwang, Jung Han; Lee, Ki Hyun; Yu, Sung Hyun (Urology Journal, 2022)
Percutaneous sclerotherapy is a safe and effective treatment for renal parapelvic cysts. However, if the cyst is in communication with the adjacent renal pelvocalyceal system, sclerotherapy is contraindicated and alternative treatment should be considered. Here, we report a case of a patient with a symptomatic renal parapelvic cyst that was treated using a novel technique involving percutaneous new tract formation between the cyst and renal pelvis.